"More than kin and less than kind": Hamlet and his (linguistic) problems - Alireza Mahdipour; Pyeaam Abbasi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2018)
T.S. Eliot's "Hamlet and His Problems" (1921) seems to be a pretext to add another erudite concept to the lexis of literary criticism. He charged both Hamlet and Hamlet of lacking "objective correlative." Eliot's own problem with the play, however, seems to arise from his particular epistemological perspective, his formalism, and even his implicit structuralism, and moreover, from his traditional, classic Cartesian modernity that suffers him to hold the notion of subject-object dichotomy in his literary speculations. Hamlet's problem, however, surpasses T. S. Eliot's structuralist view and anticipates the poststructuralist linguistic enigma. Hamlet and Hamlet's problems are, together with the other characters that are caught in the maze of language, linguistic. Hamlet's epistemological/ontological quest for the meaning or the truth are checked, patterned, done and ultimately undone by the language. He cannot find any "objective correlative" for his "particular emotion," for, in the signifying system of the language, all he can think or feel is restrained by "words". He cannot escape from the symbolic order of the language until his death, and "the rest is silence".